Photonic Spin Hall Effect: Multidimensional Manipulation of Photonic Spin Hall Effect with a Single‐Layer Dielectric Metasurface (Advanced Optical Materials 5/2019). Issue 5 (5th March 2019) - Li, Siqi; Li, Xingyi; Wang, Guoxi; Liu, Sheng; Zhang, Lingxuan; Zeng, Chao; Wang, Leiran; Sun, Qibing; Zhao, Wei; Zhang, Wenfu
Abstract : In article number 1801365, Siqi Li, Guoxi Wang, Wenfu Zhang and co‐workers present a new approach for multidimensional manipulation of the photonic spin Hall effect based on a single‐layer dielectric metasurface. This concept allows realization of the independent phase control of light with different spin states by the interplay of Pancharatnam–Berry and dynamic phases. The cover depicts the longitudinal focusing and transverse shifting of light with different spin states using the single‐layer metasurface.